Bibliometric Analysis of Cooperative Leadership Using Vosviewer Application - Siti Rosmayati; Arman Maulana (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to systematically analyze and demonstrate bibliometric analysis of data step by step using VOSViewer. A step-by-step analysis is provided to make first-time users access and utilize VOSViewers more easily. This study provides data analysis regarding Cooperative leadership so far by utilizing the mapping tool in VOSViewer. The method used is descriptive qualitative to describe the performance of bibliometric analysis by producing network visualizations of selected topics. From the search results, 25 relevant journals were found that were published in the last three years, which were then grouped into three categories according to the year of publication. After grouping journal data, researchers found that the number of articles published on the topic of cooperative leadership from 2019 to 2023 was 114 items. As a result, it is concluded that cooperative leadership is a field that can be combined with other fields to be studied. It's a way of showing lots of opportunities to discover new things to define a theme. Furthermore, this analysis is expected to be a source for researchers to conduct research and determine research themes.